Biotransformation of artemisinin and asiaticoside: Malaysian tropical plant phytochemicals - Omar, Muhammad Nor; Abu Bakar, Ibrahim; Nordin, Noor Faizul Hadry (2016)
Centella asiatica is one of the pioneering herbs that act actively in traditional remedy such as treating skin problems, including wound healing. Centella asiatica has been utilized as a traditional herbal medicine in Malaysia on different occasions and treatments including wound healing. Asiaticoside (A.S) is a major bioactive constituent in Centella asiatica as it has been reported to have antimicrobial effects and wound healing properties. Microbial transformation was extensively used to create useful metabolites from various natural products and as an alternative to chemical synthesis for the preparation of pharmacologically active compounds. This study aims to isolate A.S, the major phytochemical in Centella asiatica that plays biological activities including wound healing, which will presented for microbial transformation using Aspergillus niger fungi. Then, the wound healing activity of A.S and the asiaticoside transformed product (T.P) will be investigated, and then the effect of these products on TGFβ1 and TIMP1 gene expression will be examined to understand the mode of action of A.S and T.P on wound healing. Extraction of the phytochemicals was achieved using Soxhlet extraction with three types of organic solvents with different polarities, i.e. n-hexane, dichloromethane, and methanol. Phytochemical screening of the crude extracts showed the presence of several biological constituents and compounds, such as terpenoids and saponins, which include the targeted phytochemical A.S. The results showed that the methanolic crude extract contained the highest amount of A.S, This extract was fractionated using several techniques including liquid-liquid separation, column chromatography and size exclusion purification to afford A.S with 0.22 % recovery. Subsequently, A.S was identified by HPLC, FTIR, and NMR spectrometry. A.S with a concentration of 0.1 mg/ml was introduced into the microbial culture of A. niger and incubated for 8 days using a rotary shaker at 30 ºC. Then, extraction of the T.P was done by liquidliquid extraction to afford 50 mg of dark brown residue analyzed by TLC, 1D and 2D FTIR and proton NMR for metabolite profiling. In the third phase of the study, A.S and T.P were used in the cell proliferation and wound healing experiments using human keratinocytes. A.S and T.P showed promising results in vitro model. Results showed that A.S concentrations between 7.5 and 120 μg/ml gave higher value of cell proliferation than negative control, prompting cell proliferation improvement. The concentration of 240 μg/ml gave the lowest percentage of cell proliferation, though it did not indicate to have a cytotoxic effect, however the IC50 of A.S was ~ 446.2 μg/ml. The result showed that A.S has indeed low toxicity on human keratinocytes at the highest used concentration of 240 μg/ml. On the other hand, it was clear that T.P concentrations between 0.058 and 3.75 μg/ml exhibited the higher viability values, whereas, the concentration at 7 μg/ml showed the lowest viability value. Moreover it was detected that the concentrations from 15 to 240 μg/ml presented a severe toxicity toward human keratinocytes, IC50 value of T.P was found ~ 7.423 μg/ml, which also may confirm the change in the bioactivity properties of the original A.S. In wound healing assays analysis it was shown that there were significant differences with comparison with the negative control (P<0.05). Two-way ANOVA tests also showed that there was significant effect of the products (drugs) as well as the exposure time with P values 0.0113 and 0.0001 correspondingly. Statistical analysis showed that both A.S and T.P could increase the expression of TGFβ1 (P = 0.01 and 0.007) respectively, and the expression of TIMP1 (P = 0.0002 and 0.0006) respectively, however T.P was more effective than A.S (P = 0.009 for TGFβ1) and (0.001 for TIMP1). It was witnessed T.P showed a faster migration and healing speed under macroscopic observation. In addition it was noted that as well as T.P could considerably enhanced TIMP1 gene expression. It could be concluded that biotransformation process could produce biological active products that can be used in wound healing and pharmaceutical purposes. Since, this study was confirmed that T.P could enhance the cell proliferation and wound healing of the human keratinocytes with very low concentration in comparison to the original substrate. Meanwhile, artemisinin has remained an effective drug to treat malaria. Numerous approaches have been adapted to increase the efficacy of artemisinin against antibiotic resistant malarial parasite. Microbial biotransformation of artemisinin has been used recently to produce promising derivatives of artemisinin on a large scale with low costs. During the last decade several biotransformation studies on artemisinin, by using microorganisms, have been reported. This literature review focuses on the most recent microbial transformation studies on artemisinin and its derivatives.